Introduction to physical anthropology (West/Wadsworth, 1997)
This successful text, now in its seventh edition, offers a biocultural perspective. It integrates basic evolutionary theory, human genetics, coverage of non-human primates, paleoanthropology, and modern population biology to illustrate the physical and behavioral evolution of human beings. New research integrated throughout the text. All Guest Essays are new. A new chapter has been added on Human Growth and Development and timelines have been added before each hominid chapter. Internet resources have been added to the end of each chapter.